Social Media's Influence on Destination Choice : Trends and Insights - Chaminda Bandara; Ishani Kumaratunga; Lasith Jayawardene (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Social media platforms have become pivotal in influencing travel decisions and destination choices. This study investigates trends in user-generated content, influencer marketing, and platform analytics. Findings reveal how social media campaigns shape perceptions of destinations, contributing to increased bookings and traveler loyalty.